Religious Moderation Discourses on Digital Platforms: Upholding Diversity, Rejecting Violence, and Embracing Local Wisdom - Handayani, Rizqi; Alfida, Alfida (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2025)
This research examines the dissemination of religious moderation discourses through digital platforms, particularly YouTube, by analyzing lectures from two moderate dai, Gus Baha and Adi Hidayat. In light of social change and the evolution of digital media, the study aims to identify the values of religious moderation reflected in their messages and assess their impact on public understanding. Key research questions address the various da'wah approaches utilized on YouTube and how values such as wasathiyah (balance), tolerance, and interfaith dialogue are communicated to audiences. Employing a qualitative approach with discourse analysis, the study selects lecture videos through purposive sampling based on view count and thematic relevance. The findings reveal that both Gus Baha and Adi Hidayat effectively use digital platforms to convey moderation messages, albeit through different strategies. Gus Baha focuses on cultural narratives familiar to the community, while Adi Hidayat employs a scientific, structured approach rooted in religious texts. The analysis indicates that YouTube serves not only as a channel for disseminating moderate religious information but also plays a critical role in preventing radicalization by providing inclusive content. In conclusion, this study offers valuable insights into the role of digital media in enhancing religious moderation in Indonesia amidst complex information flows and underscores the importance of digital literacy in amplifying the positive impact of moderation messages online.